Common germline variation at the TERT locus contributes to familial clustering of myeloproliferative neoplasms. Issue 12 (26th September 2014) - Jäger, Roland; Harutyunyan, Ashot S.; Rumi, Elisa; Pietra, Daniela; Berg, Tiina; Olcaydu, Damla; Houlston, Richard S.; Cazzola, Mario; Kralovics, Robert
<x xml:space="preserve">Abstract</x> The C allele of the rs2736100 single nucleotide polymorphism located in the second intron of the TERT gene has recently been identified as a susceptibility factor for myeloproliferative neoplasms (MPN) in the Icelandic population. Here, we evaluate the role of TERT rs2736100_C in sporadic and familial MPN in the context of the previously identified JAK2 GGCC predisposition haplotype. We have confirmed the TERT rs2736100_C association in a large cohort of Italian sporadic MPN patients. The risk conferred by TERT rs2736100_C is present in all molecular and diagnostic MPN subtypes. TERT rs2736100_C and JAK2 GGCC are independently predisposing to MPN and have an additive effect on disease risk, together explaining a large fraction of the population attributable fraction (PAF = 73.06%). We found TERT rs2736100_C significantly enriched (P = 0.0090) in familial MPN compared to sporadic MPN, suggesting that low‐penetrance variants may be responsible for a substantial part of familial clustering in MPN. Am. J. Hematol. 89:1107–1110, 2014. © 2014 Wiley Periodicals, Inc.